Discussion—A Note on the Asymptotic Behavior of an Optimal Procurement Policy - Mills, Edwin S. (Management Science, 1959)
Considerable attention in recent years has been devoted to the problem of meeting known demands or requirements over some finite number of planning periods at minimum cost. Representative of these problems is a problem that was first solved in the fundamental paper by Modigliani and Hohn [Modigliani, F., F. E. Hohn. 1955. Production planning over time and the nature of the expectation and planning horizon. Econometrica 23 46–66.] (referred to as M-H). No new solutions to this problem are presented in this note. Rather the procedure is to utilize the results of the M-H paper and to investigate the behavior of the decision rule through time in a very special case which seems to be of considerable practical importance.